Nuclear Power as a Basis for Future Electrical Generation (Review) - Pioro, I.L. (Энерготехнологии и ресурсосбережение, 2014)
It is well known that the electrical-power generation is the key factor for advances in any other industries, agriculture and level of living. In general, electrical energy can be generated by: 1) non-renewable-energy sources such as coal, natural gas, oil, and nuclear; and 2) renewable-energy sources such as hydro, wind, solar, biomass, geothermal and marine. However, the main sources for electrical-energy generation are: 1) thermal — primary coal and secondary — natural gas; 2) «large» hydro and 3) nuclear. The rest of the energy sources might have visible impact just in some countries. The paper presents the current status of nuclear-power industry in the world and a comparison of nuclear-energy systems to other energy systems.